Fertilizante orgânico como fonte de fósforo no cultivo inicial de brachiaria brizantha cv. Marandú - Ourives, Ornã Enisson Almeida; Souza, Gustavo Maia; Tiritan, Carlos Sérgio; Santos, Diego Henriques [UNESP] (FapUNIFESP (SciELO), 2010)
Phosphorus is considered an essential element for plants, but it is found in low amounts in Brazilian soils, mainly in areas destined to pastures, and the application of organic matter contributes to the improvement of physical, chemical and biological soil attributes. The research had the objective of evaluating the application effects of the Bokashi organic compound on soil macro and micronutrients contents and leaves, as well as on Brachiaria brizantha cv. Marandú dry mass yield, evaluating the potential of the organic fertilizer as phosphorus source, in comparison with conventional chemical fertilizers. Different organic compound doses supplied the soil with 17 kg P2O5 ha-1, 34 kg P2O5 ha-1, 68 kg P2O5 ha-1, 136 kg P 2O5 ha-1, and 204 kg P2O5 ha-1, comparing it with the conventional chemical fertilizer and the control. The results revealed that the organic fertilizer Bokashi can adequately replace the conventional chemical fertilizer of Brachiaria brizantha cv. Marandú, supplying the soil and plant with appropriate nutrients levels and maintaining the dry mass yield.
Organic fertilizer as phosphorus supplier for Brachiaria brizantha cv. Marandú
Keywords: Bokashi; Organic fertilizers; Organic matter; Plants mineral nutrition; Brachiaria; Urochloa brizantha